Quantifying Impact of Aging Population on Fiscal Space - Park, Seok (IMF Working Papers; Working Paper ;, 2012)
This paper quantitatively investigates how population aging trend affects fiscal space measured as unused revenue generating capacity by utilizing a standard neoclassical growth model. A calibration exercise for G-7 countries shows that France, Germany and Italy suffer greater revenue impact from a given reduction in hours worked due to their larger government expenditure. Corrective measures such as pension reform and flexible expenditure policy would be required in order to mitigate the impact of aging on fiscal space.